The Islamic Ceramic of the Santarém Alcaçova: Raw Materials, Technology, and Trade. (25th April 2021) - Beltrame, M.; Sitzia, F.; Arruda, A. M.; Barrulas, P.; Barata, F. T.; Mirão, J.
Abstract : This study focuses on the analysis of Islamic ceramics from the Alcaçova of Santarém, Portugal. To establish the ceramic raw material provenance and ceramic technology, a set of raw materials was sampled and compared with the archaeological ceramics. Raw materials were dry sieved to increase the clay content, to reconstruct the ceramist homogenization process, and to evaluate chemical and mineralogical variation. Results showed that two raw materials were selected for local ceramic production, whereas some artefacts were imported.